Warmer Antarctic summers in recent decades linked to earlier stratospheric final warming occurrences - Hyesun Choi; Hataek Kwon; Seong-Joong Kim; Baek-Min Kim (Communications Earth & Environment, 2024)
Abstract Since the 2000s, the pause of the strong Antarctic cooling and later stratospheric final warming onset trends has been identified. Here we employ composite and congruence analysis using reanalysis and in-situ data to propose a linkage between pivotal changes in the surface temperature trends and the timing of stratospheric final warming events. In early stratospheric final warming events, the positive polar cap height anomaly developed in the stratosphere in early October, descending to the troposphere and surface in late spring and summer, resulting in high-pressure anomalies, which led to warmer surfaces in most of Antarctica. In late stratospheric final warming occurrences, opposing or weaker behaviors were observed. The trend toward earlier stratospheric final warming appears to play a considerable role in warmer summers over parts of interior Antarctica through the strengthening of the anti-cyclonic surface pressure anomaly. This could influence the regional sea-ice modulation over the Southern Ocean.